Exploration into Australia - Darian-Smith, Kate. (Parsippany, N.J. : New Discovery Books, 1996)
Explores the story of Australia from the earliest times, through at least 50,000 years of diverse Aboriginal societies to its exploration by Asian and European travelers, and right up to the present day.
Originally published: London : Belitha Press Ltd., 1995.
Includes index.
School Library Journal
Booklist
7.5
3-6
Keywords: Australia -- History -- Juvenile literature; Australia -- History; Australia -- History